Effect of varying N2 pressure on DC arc plasma properties and microstructure of TiAlN coatings. (17th September 2020) - Syed, B; Hsu, T-W; Chaar, A B B; Polcik, P; Kolozsvari, S; Håkansson, G; Rosen, J; Johnson, L J S; Zhirkov, I; Andersson, J M; Jöesaar, M J; Odén, M
Abstract: Detailed knowledge of correlations between direct current (DC) cathodic arc deposition process parameters, plasma properties, and the microstructure of deposited coatings are essential for a comprehensive understanding of the DC cathodic arc deposition process. In this study we have probed the plasma, generated by DC arc on a Ti-50 at.% Al cathode in a N2 ambience, at the growth front of the TiAlN coating. Several consequences of an increasing N2 pressure are observed, including a decreased electron temperature, an increased electron density, and a loss of energetic ions. As a result, the preferred growth texture switches from 220 to 111. It is also observed that neutrals in the plasma can significantly contribute to the growth of TiAlN coatings.